Product Scope and Productivity: Evidence from India's Product Reservation Policy. (17th May 2019) - Tewari, Ishani; Wilde, Joshua
Abstract : Protections for small enterprises are commonplace in developing countries. How do these policies affect overall industrial performance? Using exogenous variation in the timing of an Indian policy dismantling laws that "reserved" certain products for exclusive manufacture by small firms, we identify the effect of the dereservation policy on size, productivity, product churning, and other industry dynamics. Following the change, we find that firms significantly altered their product lines, leading to the reallocation of productive factors, increasing exits, and increasing total factor productivity. These effects were driven by new entrants moving into the formerly restricted product space, and in particular by multiproduct firms. Our findings underscore the importance of intrafirm heterogeneity on the impact of size‐contingent regulations, as firms' product line dynamics can be an important dimension of productivity growth.